Diploid male production correlates with genetic diversity in the parasitoid wasp Venturia canescens: a genetic approach with new microsatellite markers. Issue 18 (31st August 2016) - Collet, Marie; Vayssade, Chloé; Auguste, Alexandra; Mouton, Laurence; Desouhant, Emmanuel; Malausa, Thibaut; Fauvergue, Xavier
Abstract : In Hymenoptera, diploid males with null fitness are produced under complementary sex determination (CSD), when individuals are homozygous for this locus. We developed new microsatellites markers in order to assess and compare genetic diversity and diploid male proportion in populations from three distinct habitat types – mainland, island, or captive –, in the parasitoid wasp Venturia canescens . Abstract: Sex determination is ruled by haplodiploidy in Hymenoptera, with haploid males arising from unfertilized eggs and diploid females from fertilized eggs. However, diploid males with null fitness are produced under complementary sex determination (CSD), when individuals are homozygous for this locus. Diploid males are expected to be more frequent in genetically eroded populations (such as islands and captive populations), as genetic diversity at the csd locus should be low. However, only a few studies have focused on the relation between population size, genetic diversity, and the proportion of diploid males in the field. Here, we developed new microsatellite markers in order to assess and compare genetic diversity and diploid male proportion (DMP) in populations from three distinct habitat types – mainland, island, or captive –, in the parasitoid wasp Venturia canescens . Eroded genetic diversity and higher DMP were found in island and captive populations, and habitat type had large effect on genetic diversity. Therefore, DMP reflects the decreasing genetic diversity in small and isolated populations. Thus, Hymenopteran populations can be at high extinction risk due to habitat destruction or fragmentation.